2010
DOI: 10.1016/j.respe.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Migration, santé et recours aux soins à Mayotte en 2007 : enseignements d’une enquête représentative en population générale

Abstract: In this overseas French island, the migrant population is numerous and resident for a long time. Their main motivations to immigrate are economic and family-related. They report hurdles to healthcare related with their precarious living conditions, including their illegal residence status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…As in our study, these populations' poor socioeconomic conditions only partially explained their poorer perceived health [23]. A study carried out on Mayotte Island, a French overseas territory in the Comoros Archipelago, found that the health of foreigners was less good there as well (and they were found to have more difficulty accessing health care) than that of the French [24]. …”
Section: Discussionmentioning
confidence: 62%
“…As in our study, these populations' poor socioeconomic conditions only partially explained their poorer perceived health [23]. A study carried out on Mayotte Island, a French overseas territory in the Comoros Archipelago, found that the health of foreigners was less good there as well (and they were found to have more difficulty accessing health care) than that of the French [24]. …”
Section: Discussionmentioning
confidence: 62%
“…For example, migrants living on Mayotte Island, a French island in the Indian Ocean, reported barriers to healthcare related to their unstable living conditions, including their illegal residence status (Florence et al 2010). Two studies conducted in Germany of migrants from many different backgrounds found that illegal status resulted in delays in seeking care for acute and chronic medical conditions, lower quality care, difficulties accessing a regular supply of medication for chronic illnesses and poorer physical and mental health outcomes (Castaneda 2009; Kuehne et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Government and its international partners have taken considerable engagement by financing the health system, which has reduced the out-of-pocket payment by 40% since 2010. In terms of the health workforce, Comoros, like many African countries, faces a huge migration challenge of healthcare personnel to developed countries [67,68]. The latter situation has fragilized the quality of health services which could also be explained by the high overseas medical treatment experienced by the population [66,70].…”
Section: Discussionmentioning
confidence: 99%
“…Another study estimated 115 patients per year between 2004 and 2007. In addition, the French national institute of health and medical research (INSERM) estimated around 11% of the proportion of the Comorian population migrated to Mayotte for medical treatments in 2008 [67,68]. However, since the "Visa Balladur" implementation in 2005, most Comorians migrated to Madagascar, Tanzania, and Mauritius [66][67][68][69].…”
Section: Migration Of Comorian Population To Access Health Carementioning
confidence: 99%
See 1 more Smart Citation